Transitional B cells in quiescent SLE: An early checkpoint imprinted by IFN. (August 2019) - Dieudonné, Yannick; Gies, Vincent; Guffroy, Aurélien; Keime, Céline; Bird, Anna K.; Liesveld, Jane; Barnas, Jennifer L.; Poindron, Vincent; Douiri, Nawal; Soulas-Sprauel, Pauline; Martin, Thierry; Meffre, Eric; et al.
Abstract: Systemic lupus (SLE) is characterized by a break of B cell tolerance that plays a central role in disease pathophysiology. An early checkpoint defect occurs at the transitional stage leading to the survival of autoreactive B cells and consequently the production of pathogenic autoantibodies. The main purpose of our work was to determine whether transitional B cells, as the most immature naïve B cell subset upstream of pathogenic B cells, display specific features compared to healthy non SLE subjects. Through extensive analysis of transitional B cells from untreated or low treated, mostly Caucasian, SLE patients, we demonstrated that transitional (T1 and T2) B cell frequencies were increased in SLE and positively correlated with disease activity. SLE transitional B cells displayed defects in two closely inter-related molecules (i.e. TLR9 defective responses and CD19 downregulation). RNA sequencing of sorted transitional B cells from untreated patients revealed a predominant overexpression of interferon stimulated genes (ISGs) even out of flares. In addition, early transitional B cells from the bone marrow displayed the highest interferon score, reflecting a B cell interferon burden of central origin. Hence, the IFN signature in transitional B cells is not confined to African American SLE patients and exists in quiescent disease since the medullary stage. These results suggest that in SLE these 3 factors (i.e. IFN imprintment, CD19 downregulation and TLR9 responses impairment) could take part at the early transitional B cell stage in B cell tolerance by-pass, ultimately leading in periphery to the expansion of autoantibodies-secreting cells. Highlights: SLE transitional B cells display CD19 downregulation and impaired TLR9 response. IFN signature exists since the B-cell medullary stage, even out of flares. IFN signature in transitional B cells is not confined to African American SLE. IFN score correlates with the increase in peripheral transitional B cells.